2012
DOI: 10.1128/aem.02008-12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Diversity of Bartonella spp. in Small Mammals from Southeastern Asia

Abstract: f Among 1,341 blood samples from rodents that were trapped in Southeast Asia between 2008 and 2010, we found a prevalence of Bartonella infection ranging from 9.6 to 11.9%. Bartonella species identified (143 isolates) included B. elizabethae, B. coopersplainsensis, B. phoceensis, B. queenslandensis, B. rattimassiliensis, B. tribocorum, and three new putative Bartonella species. Bartonella species are intracellular parasites of erythrocytes and endothelial cells of various mammalian host species, such as humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 15 publications
2
34
0
Order By: Relevance
“…12 The pathogenicity of B. queenslandensis, which has been isolated from small mammals from several Asian countries and detected in X. cheopis fleas, is unknown. 13 The analysis of the genome of Bartonella sp. 1.1C, isolated from R. norvegicus, revealed that this species belongs to lineage 3, which contains some zoonotic pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…12 The pathogenicity of B. queenslandensis, which has been isolated from small mammals from several Asian countries and detected in X. cheopis fleas, is unknown. 13 The analysis of the genome of Bartonella sp. 1.1C, isolated from R. norvegicus, revealed that this species belongs to lineage 3, which contains some zoonotic pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…For microparasites, rodent species were investigated for hantaviruses, protists (Toxoplasma gondii, Trypanosoma levisi, and Trypanosoma levansii), Leptospira species (L. borgpetersenii; L. interrogans; L. kirshneri and L. wakefefiedae) and Bartonella sp.(B. coopersplainsensi; B. elizabethae; B. queenslandensis; B. rattimassiliensis; B.tribocorum; B. musii and B. phoceensis); (Jittapalapong et al, 2011;Jiyipong et al, 2012;Cosson et al, 2014;Pumhom et al, 2014Pumhom et al, , 2015. Table 1 summarizes the helminth species richness and microparasite species richness obtained from these published studies.…”
Section: Helminths and Microparasitesmentioning
confidence: 99%
“…These bacterial genera offer contrasting model systems for investigating the biotic factors driving the structures of associated microbial communities. Bartonella species are parasitic intracellular bacteria that infect vertebrate erythrocytes, and many species are considered to be zoonotic (16) and are linked to disease in humans (17)(18)(19)(20), including the recently identified bat-associated Bartonella mayotimonensis (21). Nycteribiids are known to host a wide variety of Bartonella spp.…”
mentioning
confidence: 99%